2022
DOI: 10.1097/ta.0000000000003604
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mental health engagement and follow-up among Black and White patients after traumatic injury

Abstract: BACKGROUND:Severe injury necessitating hospitalization is experienced by nearly three million US adults annually. Posttraumatic stress disorder and depression are prevalent clinical outcomes. The mechanisms by which programs equitably promote mental health recovery among trauma-exposed patients are understudied. We evaluated clinical outcomes and engagement among a cohort of Black and White patients enrolled in the Trauma Resilience and Recovery Program (TRRP), a stepped-care model to accelerate mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…Of these publications, 4,104 were excluded and 74 articles were included (Supplemental Digital Content, Supplementary Figure 1, http://links.lww.com/TA/D174). 2–76 A bimodal distribution shows that location and access disparities represented the majority of articles, followed by age and race (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of these publications, 4,104 were excluded and 74 articles were included (Supplemental Digital Content, Supplementary Figure 1, http://links.lww.com/TA/D174). 2–76 A bimodal distribution shows that location and access disparities represented the majority of articles, followed by age and race (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a technology-based, stepped, access-to-care model has shown high rates of acceptability and engagement among trauma survivors, including those impacted by violence . Encouragingly, similarly high rates of engagement in recommended treatment services have been observed among participants regardless of racial or ethnic background . Adapting such interventions for survivors of firearm injury and families is a clear future direction.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have pointed to the role of social determinants of health (e.g., poverty, racism, built environment/community violence) in perpetuating these disparities in the rates of violent injury and adverse psychosocial sequelae. [1][2][3]11,27,28 For instance, previous research has found that Black men who experience adverse life events, have had previous traumatic injuries, and reside in neighborhoods with higher levels of disadvantage are at heightened risk for poor recovery postinjury. 1,25 Relative to other racial groups, Black adults are more likely to experience adverse psychological outcomes (e.g., PTSD, depression) and mortality after their injury.…”
Section: Discussionmentioning
confidence: 99%
“…Using a scalable and sustainable stepped care model, TRRP provides early identification and best-practice treatments to equitably improve access to mental health care to patients who are hospitalized after violent and nonviolent traumatic injury. [11][12][13] The model includes in-hospital mental health education, screening, and enrollment in TRRP services (Step 1); automated symptom self-monitoring via daily text-messaging (Step 2); telephone-based 30-day mental health screening (Step 3); and, when appropriate, referral to evidence-based mental health treatment services (Step 4). Trauma Resilience and Recovery Program has been found to be feasible and acceptable to both adult and child traumatic injury patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation